2003
DOI: 10.1161/01.hyp.0000052542.68896.2b
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial Ultrasonic Backscatter in Hypertension

Abstract: Abstract-A disproportionate accumulation of fibrillar collagen is a characteristic feature of hypertensive heart disease, but the extent of myocardial fibrosis may differ in different models of hypertension. In experimental studies, aldosterone and endothelins emerge as important determinants of myocardial fibrosis. Changes in myocardial extracellular matrix and collagen deposition can be estimated noninvasively by analysis of the ultrasonic backscatter signal, which arises from tissue heterogeneity within the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
38
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(43 citation statements)
references
References 45 publications
4
38
1
Order By: Relevance
“…168 ± 25 a unknown unknown NO NS Kozakova et al 35 14 (64%) 163 ± 4 a 4 ± 3 known YES Concentric remodeling Matsumura et al 8 25 ( …”
Section: Studymentioning
confidence: 99%
“…168 ± 25 a unknown unknown NO NS Kozakova et al 35 14 (64%) 163 ± 4 a 4 ± 3 known YES Concentric remodeling Matsumura et al 8 25 ( …”
Section: Studymentioning
confidence: 99%
“…5 Integrated ultrasonic backscatter is a simple and widely used parameter for myocardial tissue characterization, [6][7][8][9][10] and we reported a significant correlation between myocardial integrated backscatter and LV fibrosis. 11 However, serious problems regarding standardization limit its use.…”
mentioning
confidence: 74%
“…Myocardial fibrosis could represent a substrate for the generation of malignant ventricular tachyarrhythmias, which is the current pathway for sudden cardiac death in HCM [5]. In an autopsy study in patients with HCM who died suddenly, the calculated interstitial collagen volume fraction was about 8 times greater than in control subjects and 3 times higher than in patients with essential hypertension [6], a condition well known to have interstitial fibrosis [7,8]. Fibrosis comprised 15% (up to 27%) of the transmural septal tissue sections [6].…”
Section: Introductionmentioning
confidence: 99%
“…In HCM there is an increase in the fraction of interstitial collagen, caused by the excessive synthesis of collagen I (increase of peptides released during the synthesis) not sufficiently balanced by its greater degradation for the reduced activity of metallo-proteinase catabolic (or collagenase) 1 and 2 of the matrix (MMP-1 and MMP-2) [9]. The accumulation of collagen, increasing the rigidity of left ventricle, is responsible for passive diastolic dysfunction, that is the leading cause of dyspnea [7,8,10]. In animal models with genetic mutations responsible for human HCM, it has been shown that treatment with an AT1 receptor antagonist, [11] or with simvastatin, [11] or more recently with N-acetylcysteine, [12] a precursor of glutathione, reduces the hypertrophy, the fibrosis, disarray and improves diastolic function.…”
Section: Introductionmentioning
confidence: 99%